Implementation Of The Digital Literacy Movement Program - Refanda, Farhani Rizki; Amalia, Nur (LPPM Universitas PGRI Sumatera Barat, 2024)
Indonesia is a country with a low literacy rate compared to others, making the enhancement of literacy levels for students a top priority in today's educational world. Therefore, the government has launched the Gerakan Literasi Narional to improve students' literacy rate. Additionally, with the advancement of technology, literacy has also evolved through the use of digital technology, commonly known as digital literacy. This digital literacy leverages the world of digital technology to enhance students' literacy levels, making them more creative and knowledgeable about the uses of digital technology. This research determined the implementation of digital literacy at SD Sondakan 11. This study aimed to explore the implementation of digital literacy at SD Sondakan 11 and its alignment with regulations regarding the National Literacy Movement. The research employed a descriptive qualitative method with data sources from interviews and documentation. Interviews were conducted with the school principal and the coordinating teacher. The findings showed that SD Sondakan 11 has implemented a digital literacy program by incorporating it into the curriculum as an extracurricular activity, and its implementation aligns well with the principles of the Gerakan Literasi Nasional. This research is expected to provide insights for implementing digital literacy in schools to develop students' skills and creativity in using technology as a learning tool in school.